Attitude and Knowledge towards Savings, Spending, Investment and Insurance among Students - Zuraina, Ali (Readers Insight Publisher, 2018)
The study investigates the relationship between savings attitude with spending attitude among students at tertiary level. Besides that, it attempts to find answer pertaining to students’ attitude in savings with their knowledge of investments as well as insurance. A survey research is employed as the methodology to collect the data for the current study that involves 229 undergraduate and postgraduate students in local and private universities in Malaysia. Results showed that students have a medium positive correlations between savings and speding. Likewise, they showed a medium positive correlations between savings and knowledge of investment. Nevertheless, there is a small positive correlation between savings and knowledge of insurance. The results of the study implies that there is a need to impart knowledge of insurance among the participants as the knowledge enables them to plan for their financial security and protect their lives in the future.